2020
DOI: 10.4314/aja.v9i2.199945
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric embalming using a modified Thiel method as an alternative to the formalin method

Abstract: Formalin embalming method is cheaper and commonly used. Thiel method is said to be complex, expensive, not commonly used but offers better cadavers for student teaching. The study aimed at exploring the effects of two embalming methods; modified Thiel and formalin methods on cadavers in terms of muscle softness, joint flexibility, tissue colour, formalin smell and the ease with which structures can be identified. This was an experimental study design done over the period of three months where four adult male c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…8 Consistent with the findings reported by Appaji et al and Hachabizwa et al, we found that MTS embalmed cadavers had a more natural-looking tissue colour than MFS embalmed cadavers. 8,9 In contrast, Liao et al, proposed that the tissues embalmed with the original Thiel's solution retained their natural colour as opposed to the unfavourable colour of the tissues retained by the MTS. 10 Also, the authors commented that the change in tissue colour could be due to a reduction in strong electrolytes in the MTS compared to the original Thiel solution, which could have affected the MTS's penetration power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Consistent with the findings reported by Appaji et al and Hachabizwa et al, we found that MTS embalmed cadavers had a more natural-looking tissue colour than MFS embalmed cadavers. 8,9 In contrast, Liao et al, proposed that the tissues embalmed with the original Thiel's solution retained their natural colour as opposed to the unfavourable colour of the tissues retained by the MTS. 10 Also, the authors commented that the change in tissue colour could be due to a reduction in strong electrolytes in the MTS compared to the original Thiel solution, which could have affected the MTS's penetration power.…”
Section: Discussionmentioning
confidence: 99%
“…7 The posit that the difference in tissue colour between the study groups may be attributed to the penetrating abilities of the embalming solutions. 7 Appaji et al and Hachabizwa et al reported that the colour of MTS embalmed cadavers was pale and hypopigmented close to the live tissues when compared to the formalin embalmed, which were dark brown in 8,9 The authors speculated that the varying skin tones they observed among their cadavers were due to the chemical peeling of the epidermis induced by Thiel's solution. 8 Consistent with the findings reported by Appaji et al and Hachabizwa et al, we found that MTS embalmed cadavers had a more natural-looking tissue colour than MFS embalmed cadavers.…”
Section: Discussionmentioning
confidence: 99%
“…By modifying the original embalming procedures researchers presupposed a simple method for longer persistence of cadavers and thus its use for learning intentions [10,12,23,48,68]. A visionary scientific leader Walter Thiel [24,29] presented 1992 an embalming method that maintains the natural look, colour, flexibility, and characteristics of a living body [26,27,66,67].…”
Section: History Of Human Body Preservationmentioning
confidence: 99%
“…Formalin-based compositions have been employed as an acceptable modern method of embalming irrespective of its adverse properties [22]. Formalin-embalming is also the cheapest and most popular method of commercial embalming [22,23].…”
Section: Modernmentioning
confidence: 99%
“…Formalin-based compositions have been employed as an acceptable modern method of embalming irrespective of its adverse properties [22]. Formalin-embalming is also the cheapest and most popular method of commercial embalming [22,23]. "In addition, a study carried out at the commercial embalming centres in Nigeria noted that the most popular embalming fluid which yielded the best outcome for arresting decomposing bodies (resulting from poisoning) contained a mixture of 30 litres of 20% concentrated formalin, 10 litres of 50% concentrated methanol, 150 grams of ammonium salt, 5 litres of glycerine, 60 litres of water, 10 grams of thymol and 150 grams of arterial dye" [3].…”
Section: Modernmentioning
confidence: 99%